SYNTHESIS AND FUNGICIDAL ACTIVITY OF SOME DIORGANOTIN(IV)WITH BENZAMIDOCYSTEINE - Najeeb, Dina A; Shalan, Nasser; Ibraheem, Hanan; Farina, Yang; Yousif, Emad (Al-Nahrain Journal of Science, 2009)
New diorganotin (IV) complexes of the type Ph2SnL2, Bu2SnL2 and Me2SnL2 of the ligand benzamidocysteine (LH). Ligand formed by reaction of benzoyl chloride with cysteine in presence of sodium hydroxide. The prepared complexes were characterized by elemental analysis, infrared, conductance measurements and nuclear magnetic resonance (1H,13 C and119 Sn NMR) spectral data. From the spectral measurements, monomer structures for the complexes were proposed. Bidentate and Octahedral geometry was proposed for the complexes prepared. Preliminary in vitro tests for fungicidal activity show that all prepared compounds display good activity to Gibberela, Cercospora arachidicola, Physolospora piricola and Fusarium oxysporum.